Publication trends on proportional reasoning research: A bibliometric analysis using Scopus database - Sugiarni, Rani; Abdullah , Khairul Hafezad (International Journal of Didactic Mathematics in Distance Education, 2024)
Proportional reasoning ability is an important ability for students to understand mathematical concepts. Much research has been conducted on this capability, but it is necessary to map existing research to provide a clearer picture of future research topics. This research aims to provide a bibliometric overview of trends in the use of proportional reasoning skills in mathematics teaching research. The method in this research is bibliometric analysis, which aims to analyze and classify bibliographic material by presenting a representative summary of literature in the Scopus database. The search was carried out using the keyword "proportional reasoning" in the search menu in the Scopus.com database. ScientoPy software analyzes the author's name, number of document citations, document title, publication year, document source, publisher, and document type Research trends in proportional reasoning show a significant increase, with 356 publications in Scopus, peaking at 32 in 2023. Major contributors include the United States, Turkey, and Spain, with recent studies focusing on "teacher knowledge." Influential works by Liberali et al., Atkinson et al., and Tobin & Capie address numeracy, multimedia learning, and logical thinking, respectively. These findings suggest that improving teacher knowledge and using effective multimedia tools could enhance instruction and research in proportional reasoning. Future research should explore innovative teaching strategies and technologies to further advance proportional reasoning ability.